MENINGKATKAN KEPUASAN HIDUP UNTUK MENGURANGI KELELAHAN KERJA : STUDI KASUS PADA TENAGA KESEHATAN DI PUSKESMAS KRATON PASURUAN - Hetty Murdiyani; Novia Dyah Ayuningtyas; Agus Poerwanto (Universitas Muhammadiyah Surabaya, 2025)
This study aims to determine the relationship between life satisfaction and job burnout among health workers at the Kraton Pasuruan Community Health Center. This study uses a quantitative method. The population in this study were health workers at the Kraton Pasuruan Community Health Center, with a research sample of 45 people obtained using a purposive sampling technique. Data were collected using a Likert scale model questionnaire with four answer choices. The data analysis technique was carried out using the Pearson Product Moment correlation method. The results of the hypothesis test indicate that there is a relationship between life satisfaction and job burnout among health workers at the Kraton Pasuruan Community Health Center, as indicated by the results of the hypothesis test that the correlation coefficient r value is -0.843 with a significance value of 0.000, p less than 0.01. This indicates that there is a very strong, significant, and negative relationship between life satisfaction and burnout. In other words, the higher the life satisfaction, the lower the burnout, and vice versa.